2012
DOI: 10.1111/j.1365-2869.2012.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG sigma and slow‐wave activity during NREM sleep correlate with overnight declarative and procedural memory consolidation

Abstract: SUMMARYPrevious studies suggest that sleep-specific brain activity patterns such as sleep spindles and electroencephalographic slow-wave activity contribute to the consolidation of novel memories. The generation of both sleep spindles and slow-wave activity relies on synchronized oscillations in a thalamo-cortical network that might be implicated in synaptic strengthening (spindles) and downscaling (slow-wave activity) during sleep. This study further examined the association between electroencephalographic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 26 publications
4
98
2
1
Order By: Relevance
“…In some studies the increase in spindle activity was topographically restricted to the cortex areas most strongly involved in skill performance, i.e., in the contralateral motor cortex after motor tapping training (862) and in the parietal cortex after training in a visuospatial skill (214). Also, correlations between different parameters of spindle activity or stage 2 sleep and overnight improvements in motor skills have been consistently reported (562,862,1216,1286,1287), and these correlations were revealed for fast rather than slow spindles, in the studies distinguishing these two spindle types (59, 962,1174).…”
Section: Sleep and Memorymentioning
confidence: 94%
See 1 more Smart Citation
“…In some studies the increase in spindle activity was topographically restricted to the cortex areas most strongly involved in skill performance, i.e., in the contralateral motor cortex after motor tapping training (862) and in the parietal cortex after training in a visuospatial skill (214). Also, correlations between different parameters of spindle activity or stage 2 sleep and overnight improvements in motor skills have been consistently reported (562,862,1216,1286,1287), and these correlations were revealed for fast rather than slow spindles, in the studies distinguishing these two spindle types (59, 962,1174).…”
Section: Sleep and Memorymentioning
confidence: 94%
“…In rats, robust increases in sleep spindles (12)(13)(14)(15) Hz) were observed after learning odor-reward associations (354) and after avoidance training (397). Furthermore, indicators of sleep spindle expression consistently correlated with the amount of overnight retention of declarative memories (86,213,214,235,446,562,822,1016,1024,1037,1044,1057). Interestingly, spindle activity (11)(12)(13)(14)(15) Hz) also correlated with signs of overnight lexical integration of newly learned information, suggesting that spindles contribute to the integration of new memories into existing neocortical knowledge networks (1175).…”
Section: Relationship Between Spindles and Memorymentioning
confidence: 97%
“…Numerous studies have demonstrated the importance of SWS and associated EEG slow oscillatory activity for the consolidation of hippocampus-dependent psychological memories [4,82]. Immunological studies identified SWS as part of the immune response that facilitates recovery from infections [69,83].…”
Section: Are There Shared Mechanisms Of Sleep-dependent Memory Formatmentioning
confidence: 99%
“…Sleep EEG spectral analysis was carried out to assess power spectra as described previously (eg, Holz et al, 2012;Nissen et al, 2001). The analysis was performed on the C3-A2 derivation in 30-s epochs for which sleep stages had been determined.…”
Section: Sleep Recordingsmentioning
confidence: 99%